2009
DOI: 10.1007/bf03326113
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical distribution of trace metal pollutants in water and sediments of downstream of an urban river

Abstract: ABSTRACT:A study was conducted to investigate the trace metal pollution of water and sediments of downstream of Tsurumi River, Yokohama, Japan. Twenty samples of water and sediments were collected from the river starting from Tokyo bay side up to the junction point of the Yagami River. Results show that the mean concentrations of chromium, cupper and nickel in water greatly exceed (>100 times) the surface water standard. The concentration of molybdenum and lead was also higher than standard values while iron a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
103
3
13

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 230 publications
(131 citation statements)
references
References 34 publications
6
103
3
13
Order By: Relevance
“…The concentration of Pb was high in the north, south, and west regions, compared with low concentration in the east region and core zone (P \ 0.05). The spatial distribution of the metals, however, indicated that it had been apparently affected by the surrounding agriculture and industry (Mohiuddin et al 2010;Karbassi et al 2006). In the north region of the study area, the concentrations of metals (except for Pb) were high.…”
Section: Resultsmentioning
confidence: 99%
“…The concentration of Pb was high in the north, south, and west regions, compared with low concentration in the east region and core zone (P \ 0.05). The spatial distribution of the metals, however, indicated that it had been apparently affected by the surrounding agriculture and industry (Mohiuddin et al 2010;Karbassi et al 2006). In the north region of the study area, the concentrations of metals (except for Pb) were high.…”
Section: Resultsmentioning
confidence: 99%
“…Heavy metals in sediments are controlled by innumerable factors that include the concentration of metals in rocks at the time of formation of sediments and anthropogenic sources of pollution [38][39][40][41][42]. The results of Pearson's correlation coefficients and their significance levels (P<0.01 and P<0.05) are shown in Table 2 .01) in Namal Lake sediments indicates that these metals originated from the same sources or were distributed in the surface by the same physico-chemical processes [43][44].…”
Section: Pearson's Correlation Coefficient Analysismentioning
confidence: 99%
“…According to Mohiuddin et al (2010), PLI = 0 indicates a perfect state of pollution; PLI = 1 points indicate only baseline levels of pollutants present and PLI [1 would indicate progressive deterioration of sites.…”
Section: Pollution Load Index (Pli)mentioning
confidence: 99%